Peripheral Nerve Disorders and Treatment - Turker, Hande; Garcia Benavides, Leonel; Ramos Gallardo, Guillermo; Méndez Del Villar, Miriam (IntechOpen, 2020)
Neuropathies are one of the main neurological problems in everyday life, and they still have many partially understood parts and unknowns both for physicians and patients. Many systemic conditions may exist within them and therefore they may be difficult to treat. In this book we provide current knowledge concerning neuropathies, which we believe you will find interesting. The subject ''neuropathies'' comprises a number of topics, and each and every one could be the subject of a textbook. On the other hand, this book was never designed as one. This book should be read without prejudgment because the content may not be compatible with general but repeated assumptions and guidelines. However, I believe that the book may be an inspiration for many young investigators as well. It contains current approaches and knowledge and we sincerely believe and hope that it will answer your queries regarding new perspectives about neuropathy in general.